2015
DOI: 10.1158/1078-0432.ccr-14-2842
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Expression in 21-Gene Recurrence Score Predicts Increased Late Recurrence for Estrogen-Positive/HER2-Negative Breast Cancer

Abstract: Purpose: To identify the individual genes or gene modules that lead to the OncoptypeDx 21-gene recurrence score's reduced performance after 5 years and thereby identify indices of residual risk that may guide selection of patients for extended adjuvant therapy.Experimental Design: We conducted a retrospective assessment of the relationship between (i) the individual genes and gene modules of the Recurrence Score and (ii) early (0-5 years) and late (5-10 years) recurrence rates in 1,125 postmenopausal patients … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 25 publications
7
34
2
1
Order By: Relevance
“…Other studies have found that DUSP4 mRNA expression inversely correlated with a gene-expressionbased Ras-ERK pathway score in 230 primary breast cancers (11), and in 633 breast tumors from The Cancer Genome Atlas we observed an inverse correlation with BRAF and DUSP4 mRNA expression (Supplementary Table S3 À patients. Notably, HER2 expression was significantly associated with risk of relapse even in the HER2 À cohort, with low rather than high expression associated with greater risk, consistent with our previous reports on the ABC and ATAC adjutant trials (54,55). This may be partly due to a direct relationship between ER and HER2 expression in the HER2 À group (with higher ER expression being linked to better prognosis) or to loss of that locus on chromosome 17 in genetically unstable, poorer prognosis tumors.…”
Section: /Her2supporting
confidence: 90%
“…Other studies have found that DUSP4 mRNA expression inversely correlated with a gene-expressionbased Ras-ERK pathway score in 230 primary breast cancers (11), and in 633 breast tumors from The Cancer Genome Atlas we observed an inverse correlation with BRAF and DUSP4 mRNA expression (Supplementary Table S3 À patients. Notably, HER2 expression was significantly associated with risk of relapse even in the HER2 À cohort, with low rather than high expression associated with greater risk, consistent with our previous reports on the ABC and ATAC adjutant trials (54,55). This may be partly due to a direct relationship between ER and HER2 expression in the HER2 À group (with higher ER expression being linked to better prognosis) or to loss of that locus on chromosome 17 in genetically unstable, poorer prognosis tumors.…”
Section: /Her2supporting
confidence: 90%
“…The study found that Oncotype RS is strongly prognostic for late distant recurrence in women with a high ESR1 level (cut-off 9.1) and that extended tamoxifen therapy is warranted in those with high expression of ESR1 and intermediate/high risk patients. In contrast to this study, an exploratory analysis of the individual Oncotype RS genes in the transATAC cohort revealed that for oestrogen-related genes the prediction of distant recurrence was substantially different between early versus late follow-up period [17]. These differential findings need to be confirmed and a clearer understanding gained of whether a certain ESR1 level is needed for the use of Oncotype RS in the context of predicting late distant recurrence.…”
Section: Biomarker Assayscontrasting
confidence: 79%
“…Other results [10] also demonstrated that proliferation-related factors, such as Ki67 or clinical tumour grade, are not prognostic for late distant recurrence. This is in contrast to the proliferation-related genes in the Oncotype RS, where similar recurrence risk and prognostic abilities were found for early and late time periods [17]. The BCI identifies women with node-negative disease at increased risk of late distant recurrence and might be used in the clinical setting to identify women who might benefit from further endocrine therapy.…”
Section: Breast Cancer Indexmentioning
confidence: 88%
“…Moreover, host factors may influence tumor biology. To date, most studies analyzing prognostic factors for early and late relapse have been performed in postmenopausal women, mainly using patients and samples in adjuvant aromatase inhibitor trials [10][11][12][13], in which patients received tamoxifen or aromatase inhibitors as adjuvant endocrine therapy. Kennecke and colleagues retrospectively analyzed risk of early [14] and late recurrence [15] among postmenopausal women with ER-positive early breast cancer treated with adjuvant tamoxifen.…”
Section: Introductionmentioning
confidence: 99%